An Uneven Playing Field: Athlete Injury, Illness, Load, and Daily Training Environment in the Year Before the FINA (Aquatics) World Championships, 2017. Issue 6 (November 2021) - Mountjoy, Margo; Junge, Astrid; Slysz, Josh; Miller, Jim
Abstract : Objective: To assess athlete's training environment and health problems before the FINA World Championships (WC) (2017) and to analyze the differences between the 6 disciplines, gender, and countries with different medal rankings during the championships. Design: Retrospective anonymous questionnaire. Setting: FINA WC 2017. Participants: Registered aquatic athletes (swimmers, divers, high divers, water polo players, artistic swimmers, open water swimmers). Main Outcome Measures: The outcome measures included the following: training and competition load, availability of support staff, performance of injury prevention exercises, and prevalence of health problems. The independent variables included gender, aquatic discipline, and country group based on medal ranking. Results: In the 12 months preceding the Championships, 67% of the athletes reported physical complaints and 41% trained or competed with a diagnosed injury. Only half of the athletes reported that injury prevention exercises were always (29.9%) or often (23.4%) a regular part of their daily training. In the daily training environment, support staff (excluding coach) was not available or available only if the athlete pays in 28.4% (specialized trainer) to 58.9% (sport scientist) of cases. About one-quarter of the athletes rated the support offered by their National Team program as poor or very poor. There were discrepancies in training loads and support staff among the 6 aquatic disciplines. Availability of support staff, athlete's satisfaction with their training environment/support, and regular use of injury prevention exercises were higher in countries that ranked higher in the medal list. Conclusions: Injury prevention strategies should be promoted in aquatic sports, with prospective surveillance for the early identification of physical complaints. The facilitation of access to sport-specific experts could improve athlete's health and performance, especially in countries with low medal ranking.